ATM yapısının analizi ve sistem tasarımı - Göktaş, Haluk (My University, 1997)
ABSTRACT In 1980s as a result of the development of the technological in optical fiber and VLSI, idea that is to transfer services at high speed, was created. The high speed transmission of the data, voice etc. Service was provided by ISDN. The performance limitation of the ISDN, which is also called Narrowband ISDN, was insufficient after meanwhile. ATM (Asynchronous Transfer Mode) that is proposed to make transmission at packet switching transfer, multiplexing faster, is the implementation of the B-ISDN. The ATM is the independent- of physical layer and it provides packet switching at high medium that ATM is used to, is SONET. (Synchronous Optical Network) At the medium speed is 155.2 Mbps to 622.5 Mbps. And also it can be used much great than the speed. The proposes of the thesis is to make fundamental of the ATM, interface and networking of it and to design ATM system.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Atm yapısı; Atm protokol ve fonksiyonu; Atm teknoloji ve network